Floods affect the abundance of invasive Impatiens glandulifera and its spread from river corridors. Issue 4 (26th January 2017) - Čuda, Jan; Rumlerová, Zuzana; Brůna, Josef; Skálová, Hana; Pyšek, Petr
Abstract: Aim: Riparian habitats are amongst the most invaded ecosystems world‐wide. The great abundance of invasive species in river corridors is attributed to the efficient transport of alien species' propagules and reduced competition from native plants due to regular flooding. Once an invasive species has become established, river corridors can serve as stepping stones for spread into other habitats. We have chosen the Himalayan balsam Impatiens glandulifera Royle, highly invasive annual in riparian areas, as a model for spread of invasive species from linear river corridors. Location: Central Europe. Methods: We mapped its distribution and recorded its abundance in over 1200 patches along four rivers in central Europe, differing in the time of balsam's introduction (1900–1995). The patches were characterized in terms of the distance from the riverbank, height above the river surface, degree of soil disturbance and flooding regime. Results: The patches at sites subject to flooding had twice as many individuals as those that were not subject to flooding, regardless of their distance from the riverbank and height above the river surface. There was a strong effect of the river identity, with river invaded 20 years ago being less infested than those invaded earlier. The distance from the riverbank at which the populations occurred differed and did not depend on river identity/residence time. The patches in tributaries were on average two times further from the bank of the main river than those located elsewhere. Main conclusions: Flooding is an important factor affecting the abundance of I. glandulifera, and accounts for its spread and dominance along river corridors probably due to spreading the seeds, increasing nutrient availability and disturbing native vegetation. It is likely that the number of I. glandulifera populations will increase in the future, especially along small water courses.